2021
DOI: 10.3389/fbioe.2021.705774
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Spray vs. Electrochemical Deposition: Toward a Better Osteogenic Effect of Hydroxyapatite Coatings on 3D-Printed Titanium Scaffolds

Abstract: Surface modification of three-dimensional (3D)-printed titanium (Ti) scaffolds with hydroxyapatite (HA) has been a research hotspot in biomedical engineering. However, unlike HA coatings on a plain surface, 3D-printed Ti scaffolds have inherent porous structures that influence the characteristics of HA coatings and osteointegration. In the present study, HA coatings were successfully fabricated on 3D-printed Ti scaffolds using plasma spray and electrochemical deposition, named plasma sprayed HA (PSHA) and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…However, the complex pathogenesis of OA, relevant cellular pathways, and therapeutic approaches have not been fully elucidated. Many methods of modifying the cell phenotype and promoting cartilage matrix regeneration are being investigated, and regulating cellular homeostasis is known to be a critical factor in altering the progression of and treating OA ( Shi et al, 2019 ; Zhang et al, 2019 ; Ito et al, 2021 ; Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the complex pathogenesis of OA, relevant cellular pathways, and therapeutic approaches have not been fully elucidated. Many methods of modifying the cell phenotype and promoting cartilage matrix regeneration are being investigated, and regulating cellular homeostasis is known to be a critical factor in altering the progression of and treating OA ( Shi et al, 2019 ; Zhang et al, 2019 ; Ito et al, 2021 ; Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our present study demonstrated that when combined with tumor comprehensive treatment, 3D-printed spinal implant surgery provides patients with excellent long-term spinal function and low risk of local tumor recurrence. Future directions may show further promise with modifications of the surface of the 3D-printed spinal implants to allow for enhanced osteogenic effects and anti-tumor activity[ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The technical details and behavior of the plasma spray (PS) process, HVOF, and cold spray (CS) techniques have been com-pared and tabulated in Table 7. Recently, Sun et al 235 compared PS and electrochemical deposition techniques in depositing HA on a 3D printed titanium substrate. The inherent porosity of the 3D printed substrate influenced the coating behavior and osseointegration properties.…”
Section: Comparison Of Different Thermal Spray Techniquesmentioning
confidence: 99%
“…101,179,432,433 Thus, future studies require the scrutinization of the optimum and best additives in the HA matrix and the paramount coating techniques, which can reduce the degradation, enhance the durability and non-infectious nature of the bone implants devoid of negotiation in the biocompatibility of the materials. Recently, Sun et al 235 investigated the surface modifications of 3D printed scaffolds by the plasma spray process, which resulted in a smooth and continuous surface, thus promoting mesenchymal stem cells proliferation in vitro and bone repairability in vivo. A very recent review by Li et al 434 highlighted that 3D and 4D bioprinted implants were facing challenges in the bioactive functionalization of surfaces.…”
Section: Review Biomaterials Sciencementioning
confidence: 99%
See 1 more Smart Citation